Grinder Edge Variation Test of Multifucer Coffee Grinder - Tarida Lestari Lumbangaol; Ainun Rohanah; Lukman Adlin Harahap (Jurnal Rekayasa Pangan dan Pertanian, 2016)
This research was done to test the effect of grinder edge on the effective capacity of the equipment,  percentage of losses material, and percentage of yield. This research was using non factorial completely randomized design. It was found that the capacity of the equipment,  percentage of losses material, and percentage of yield on two grinder edge are 12,72 kg/hour, 7,00%, dan 93,00% respectively.  On three grinder edge are 16,44 kg/hour, 7,67%, dan 92,33% respectively. On four grinder edge are 16,01 kg/hour, 9,00% dan 91,00% respectively. The results showed  that number of grinder edge had significant effect on the effective capacity, and had no effect on the percentage of losses material, and percentage of yield. Keywords : Grinder edge, grinder, arabica coffeaa